Decoupling the electrical resistivity contribution of grain boundaries in dilute Fe-alloyed Cu thin films. (June 2023) - Bishara, Hanna; Langenohl, Lena; Zhou, Xuyang; Gault, Baptiste; Best, James P.; Dehm, Gerhard
Abstract: To study the role of chemical composition on the resistivities of grains and grain boundaries (GB) for dilute Fe-alloyed Cu thin films, Cu films with grain sizes varying over three orders of magnitude and compositions of 0.025 and 0.25 at.% Fe were prepared by magnetron co-sputtering. Character, morphology and compositions of bulk and GBs were studied using electron backscatter diffraction, transmission electron microscopy and atom probe tomography, respectively. The specific resistivities of both individual GBs and within grains were obtained through local electrical measurements assisted by micromanipulation in situ within a scanning electron microscope. In addition, global resistivity characterisation of the thin films allowed for calculation of the GB reflection coefficient. A decoupling of GB and grain interior resistivities is found with alloying, where the GB resistivity increases by an order of magnitude while the grain interior is affected only to a minor extent in comparison. Graphical abstract: Image, graphical abstract